GRADE V STUDENTS' CREATIVITY: MAKING SIMPLE DRINK PRODUCTS FROM ALOE VERA AT MIS HANDAYANI PONTIANAK - Herianty, Afrilya; Setyaningsih, Kristia; Buchori, Achmad (Schola, 2024)
This research examines the development of creativity in fifth-grade students at MIS Handayani Pontianak through a project-based learning approach focused on making aloe vera beverage products. The integration of edupreneurship education combined with entrepreneurial principles aims to cultivate essential skills such as creativity, independence, and critical thinking. Using a qualitative case study design, data were gathered through observation, interviews, and documentation to capture the stages of the learning process: planning, production, promotion, and evaluation. In the planning stage, students brainstormed and budgeted for unique aloe vera drink ideas, learning to calculate production costs and manage resources. During production, students gained hands-on experience in preparing aloe vera and exploring flavor variations, enhancing both their practical skills and willingness to experiment. The promotion stage helped students develop communication and branding skills as they designed logos and promotional materials, while the evaluation stage encouraged self-reflection on product quality, process effectiveness, and improvement opportunities. These activities reinforced basic economic concepts, such as cost estimation, pricing, and profit calculation, as practiced during Market Day. The project demonstrated that project-based edupreneurship activities improve students' creativity, problem-solving, and collaboration abilities while fostering an entrepreneurial mindset. This study recommends integrating similar programs into school curricula, leveraging local resources for sustainable product ideas, and providing entrepreneurship training for teachers to further support students. Involving parents and the community can enhance learning outcomes and provide students with a platform to showcase their work, helping to instill a foundational understanding of entrepreneurship from an early age